Datafied ageing futures: Regimes of anticipation and participatory futuring - Juliane Jarke; Helen Manchester (Big Data & Society)
With this paper we join others in their call to resist and challenge regimes of anticipations that suggest our futures are inevitably linked to certain imaginaries about data-driven systems. The future is not simply happening but is made now – through regimes of anticipation that shape our expectations, imaginaries, visions and hypes, and define what is thinkable and desirable. Who or what is able to claim the future is an exercise of power and a matter of social justice. However, current anticipations circulating about datafied futures are often determined by powerful social actors such as states or technology companies. In this paper, we explore how we might open up futures-making to different people in relation to futures of ageing. Central is the question of whether and how we can actually think (and imagine) outside of powerful anticipation regimes around the increasing spread and relevance of data-driven systems and/or ageist assumptions about how to ‘fix’ the problem of demographic ageing. We draw on data from a series of design fiction workshops with older adults, civil society organisations and civil servants in Germany, Austria and the UK. Our analysis explores how participatory futuring might allow participants to question their own assumptions and anticipations about the futures of data-driven technologies in ageing societies but that, due to ‘discursive closure’, this may not lead to radically different futures imaginaries.